Adaptive hand-to-hand combat as a means of restoring motor functions in individuals with lower limb amputation defects - Radchenko , Yu.; Radchenko , A.; Nosova , N.; Labinska , G.; Zhirnov , O. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. Every year, one million limb amputations are registered in the world. Today, this issue is becoming relevant in Ukraine. In recent years, the number of people with lower limb amputations has been constantly increasing, due to the differences in the conduct of military operations in Ukraine. According to various estimates, the number of amputations in Ukraine ranges from 50 to 200 thousand. Physical education and sports rehabilitation occupies an important place in the process of recovery of people with disabilities. One of the types of physical education and sports rehabilitation is adaptive sports. This is a type of adaptive physical culture, which aims to meet the needs of a person with disabilities in self-affirmation, socialization and communication. The purpose of the study consists in determining the features of adaptive hand-to-hand combat as a tool for restoring motor functions in people with amputation defects of the lower extremities. Research methods: The work uses theoretical analysis and generalization of special scientific and methodological literature on the assessment of technical and tactical preparedness in martial arts, pedagogical observations, conversations, questionnaires, and generalization of best practices of specialists. Results. Engaging in various sports is one of the main and effective means of restoring motor functions in people with lower limb amputation defects. At the same time, this type of activity requires a significant amount of motor actions and types of competitive activity to develop individual recovery programs at different stages of rehabilitation, taking into account the peculiarities of the nosology and biomechanics of people with different levels of lower limb amputation. Hand-to-hand combat, thanks to its variety of training and competitive activities, a wide range of methods and tools, can occupy an important place in the comprehensive restoration of motor functions in people with lower limb amputation defects. However, despite the various types of training and competitive activities, only the discipline “Technique Demonstration” is optimally suitable for adaptive hand-to-hand combat. The structure of the training system in adaptive sports in terms of its main components has much in common with the general system of training of athletes but must necessarily take into account the nosological determinism of the structure and content of the training system and the need for a rehabilitation and social-adaptive orientation of training and competitive activities. Competitive activity is an important component of the process of sports training in general and adaptive hand-to-hand combat in particular, but scientists, draw attention to the fact that in high-performance sports the result mostly depends on the athlete's abilities, and in adaptive sports the result depends on the preservation of motor capabilities. Conclusions. The effectiveness of using adaptive hand-to-hand combat as a tool for restoring motor functions and the functional state of people with lower limb amputation defects depends on the length of the stump, the functionality of the prosthesis, and adherence to a specific algorithm and developed methodological recommendations for organizing training and competition processes.